Cinema within the Aesthetic Relation: Film Studies and Gérard Genette’s Art Theory (Cinéma & Cie. Film and Media Studies Journal, 2012)
Throughout their histories, film theory and analytical aesthetics have rarely shown points of contact. This paper attempts to overcome this impasse by showing the suitability of Genette’s aesthetics to film studies while tracing a broader reconnaissance of these misconnections. This essay is divided into two parts. First, it identifies the reasons that have hindered the inter- actions between analytic aesthetics and film studies. Second, it addresses the compatibility of some of the concepts Genette presents in his magnum opus The Aesthetic Relation to con- temporary film studies.